Diversity and abundance of birds devastating rice-growing in the town of Daloa and its outskirts (Centre-West, Cote d'Ivoire) - Allou Dimitri Kouadio; Dibie Bernard Ahon; Gnininte Maxime Zean; Wadja Mathieu Egnankou; Bene Jean-Claude Koffi; Yao Tano (European Scientific Journal, ESJ, 2024)
Rice devastating birds are responsible for many losses in rice fields around the world. In Cote d'Ivoire, data on birds in inland are almost non-existent. A study on these birds was carried out from November to December 2019 in three rice fields (Zepreguhe, Abattoir and Kennedy) in the town of Daloa and its outskirts. The study aimed to know the population of those birds in this area. The main method used was the fixed-point, time-dependent counts or point-in-time abundance index (PIA) method. It was possible to count 2368 individuals of 41 species belonging to 14 families of eight orders. The Shannon-Wiever diversity (H'); equitability (E); dominance (IDO) and IPA indices of rice devastating birds in this zone are 3.03, 0.82, 24.79 and 135 respectively. The best-represented family is the Ploceidae with 12 species and 882 individuals. The Village Weaver Ploceus cucullatus and the Northern Grey-headed Sparrow Passer griseus represent the two most abundant species with numbers of 368 and 219 individuals respectively. Of the three study sites, the Zepreguhe site is the most important in terms of specific richness (38 species), relative abundance (37.54%) and PIA (PIA = 155). Further studies are planned to monitor the diversity and population dynamics of these birds over the long term and to determine the extent of their impact on rice production in this area.